Differences in the distribution of HER2-positive breast tumors according to ethnicity and genetic variants in ERBB2: a special focus on Asian and Latina women - Laura Rey-Vargas; Laura Rey-Vargas; Lina María Bejarano-Rivera; Patricia López-Correa; Diego Felipe Ballen-Lozano; Silvia J. Serrano-Gómez; Silvia J. Serrano-Gómez (Frontiers in Oncology)
BackgroundHER2-positive breast tumors are clinically important breast cancer subtypes with an overall unfavorable prognosis, but also with current optimal treatment options that have significantly improved the patients’ survival. Several epidemiological registries have reported varying prevalence rates of HER2-positive breast tumors among population groups. In this review, we describe the prevalence of HER2-positive breast tumors by ethnicity, with a special focus on Asian and Latina women, along with genetic variants located in or near ERBB2 that might affect its protein expression.MethodsWe conducted a literature search for studies reporting differences in HER2-positive breast tumor prevalence among populations and HER2/ERBB2 molecular features based on genomic background or ancestry.ResultsOverall, Asian and Latina women tend to have higher proportions of HER2-amplified tumors, compared to non-Hispanic white (NHW) women. Additionally, higher Indigenous American ancestry is associated with an increased likelihood of HER2-positive tumors and elevated ERBB2 expression. We also describe reported differences in the genotype of several genetic variants in ERBB2 or nearby genomic regions according to HER2 expression, and mention variants in other genes that may also be associated.ConclusionsThis literature review contributes to a better understanding of the underlying biology of HER2 expression in breast tumors, and the possible mechanisms that explain the differences in the distribution of HER2-positive subtypes among various population groups.